Kıbrıs Türk Ağızlarında Ünlülerle Başlayan Sözlükbirimler - Betmezoğlu, Meryem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
In this study presented as a Master‟s Thesis for Eastern Mediterranean University‟s Institute of Graduate Studies and Research, Department of Turkish Language and Literature, in accordance with the three dictionaries of Cypriot Turkish dialect that has been written so far, lexemes (that start with vowels) have been phonetically, morphologically, semantically and etymologically analyzed. Lexemes which are used in the Turkish Cypriot dialect with the same morphology and semantics as standard Turkish of Turkey are not included in the study. By comparing the Lexemes which differ in terms phonetics and semantics from those forms used in the standard Turkish of Turkey, with the forms in Anatolian dialect, it has been attempted to determine the phonetic similarities or the semantic proximities between Anatolian and Turkish Cypriot dialects. Etymological analysis has also been carried out when necessary. The main objective of the study is to contribute to studies about Northern Cyprus‟ ethnic structure by determining common lexemes of Turkish Cypriot dialects and Anatolian dialects, thus providing data that will correlate ethnicity with dialect. Therefore, in this study, the regions where lexemes correspond to those in Anatolian dialect in terms of phonetics and semantics has been attempted to be shown as they are in Anadolu Ağızları Derleme Sözlüğü (Dictionary of Anatolian Dialects), unless they were too widespread. In the introduction section of the study, general information regarding the topic of the study, its aims, importance and research methods has been provided. In the second section, the ethnic structure of Northern Cyprus has been elaborated and exiles and migrations since the conquest of the Ottoman Empire have been pointed out. In the third section, lexemes which differ from standard Turkish of Turkey scanned from three Cypriot Turkish dialect dictionaries that are the main source of this study have been studied; their similarities and differences with Anatolian dialects were attempted to be determined. The morphology of derivative and compound words; the intended meaning (the aim) with the units that are used as vehicles and take place in the construction of idioms has been analyzed. Commonalities with the Anatolian dialects have been determined. In the fourth section, lexemes that are characteristic of Turkish Cypriot dialects which start with vowels have been attempted to be classified within themselves. Borrowed lexemes (Arabic, Persian, Romaic and English) have been brought together; and the Turkish units, elements that are never used in Turkish of Turkey, that are created, derived by the Turkish Cypriots; units that are included in Turkish Cypriot dialects but that differ from Anatolian dialects in phonetics and semantics have been brought together under separate headings. Archaic elements that can be seen in Turkish Cypriot dialects and examples which have been transformed by analogy to their Romaic morphologies have also been specified. In the fifth section, the amount of commonality the determined words have with particular provinces in Anatolian dialects have been indicated by numbers, also, it has been attempted to determine the Anatolian province from which Northern Cyprus let in the most immigrants-exiles by comparing the obtained data to migration and exile information given in the first section; it has been investigated whether or not historical information can be verified using data provided by the language. Keywords: Turkish Cypriot dialects, Anatolian dialects, comparative dialect studies, ethnic structure and dialect, lexemes, vocabulary.

ÖZ : Doğu Akdeniz Üniversitesi Lisansüstü Eğitim, Öğretim ve AraĢtırma Enstitüsü Türk Dili ve Edebiyatı Bölümü Yüksek Lisans tezi olarak ortaya koyduğumuz bu çalıĢmada Kıbrıs Türk ağızlarının bugüne kadar yazılmıĢ üç sözlüğünden hareketle sözlükbirimler (ünlülerle baĢlayanlar) ele alınmıĢ ve ses, yapı, anlam ve köken bakımından incelenmiĢtir. ÇalıĢmada, Kıbrıs Türk ağızlarında ölçünlü dildeki biçim ve anlamıyla kullanılan sözlükbirimlere yer verilmemiĢtir. Ölçünlü dildeki biçiminden ses ve anlam farklılığı gösteren birimler, Anadolu ağızlarındaki biçimleriyle karĢılaĢtırılarak, Anadolu ile Kıbrıs Türk ağızları arasındaki ses benzerlikleri ya da anlam yakınlıkları tespit edilmeye çalıĢılmıĢtır. Gereken yerlerde köken araĢtırılmasına da gidilmiĢtir. ÇalıĢmamızdaki esas amaç Kıbrıs Türk ağızları ile Anadolu ağızlarının ortak sözlükbirimlerini belirleyip, etnik yapı ile ağız arasındaki bağı kuracak veriler sunarak, Kuzey Kıbrıs‟ın etnik yapısı ile ilgili yapılan çalıĢmalara, katkıda bulunmaktır. Bu nedenle çalıĢmamızda, Anadolu ağızlarındakiyle ses ve anlam açısından örtüĢen sözlükbirimlerin geçtiği yöreler de, çok yaygın olmadıkça, Anadolu Ağızları Derleme Sözlüğü‟ndeki biçimiyle gösterilmeye çalıĢılmıĢtır. ÇalıĢmanın giriĢ kısmında, araĢtırmanın konusu, amacı, önemi, araĢtırma teknikleri hakkında genel bilgiler verilmiĢtir. Ġkinci bölümde, Kuzey Kıbrıs‟ın etnik yapısı üzerinde durulmuĢ, Osmanlı‟nın Ada‟yı fethinden itibaren baĢlayan sürgünlere ve göçlere dikkat çekilmiĢtir. Üçüncü bölümde, çalıĢmamızın temel kaynağı olan üç Kıbrıs Türk Ağzı sözlüğünden taranan, ölçünlü dilden farklılık gösteren sözlükbirimler, incelenmiĢ; Anadolu ağızları ile benzeĢen yanları ve ayrılan yönleri belirlenmeye çalıĢılmıĢtır. TüremiĢ ve birleĢik sözcüklerin yapısı; deyimlerin kuruluĢunda yer alan araç olarak kullanılan birimlerle anlatılmak istenenin (amacın) çözümlenmesi yoluna gidilmiĢtir. Anadolu ağızları ile olan ortaklıklar tespit edilmiĢtir. Dördüncü bölümde, ünlü ile baĢlayan, Kıbrıs Türk ağızlarına özgü söyleyiĢiyle sözlükbirimler kendi içinde sınıflandırılmaya çalıĢılmıĢtır. Alıntı sözlükbirimler (Arapça, Farsça, Rumca ve Ġngilizce) toplanmıĢ; Türkçe birimler de, Türkiye Türkçesinde hiç kullanılmayan, Kıbrıs Türkünün yarattığı, türettiği öğeler; Kıbrıs Türk ağızlarında olup Anadolu ağızlarından ses ve anlam farklılığı gösterenler ayrı ayrı baĢlıklar altında toplanmıĢtır. Kıbrıs Türk ağızlarında görülen eskicil öğeler ve Rumcadaki biçimine örnekseme ile Ģekil değiĢtirmiĢ örnekler ayrıca belirtilmiĢtir. BeĢinci bölümde, tespit edilen sözcüklerin Anadolu ağızlarında hangi illerle ne kadar ortaklık gösterdiği rakamlarla belirtilmiĢ, ayrıca elde edilen bu veriler, birinci bölümde verilen sürgün ve göç bilgileri ile karĢılaĢtırılarak, Kuzey Kıbrıs‟ın, Anadolu‟nun en fazla hangi ilinden göç-sürgün aldığı belirlenmeye çalıĢılmıĢ; dilin sunduğu verilerle tarihî bilgilerin doğrulanıp doğrulanamayacağı araĢtırılmıĢtır. Anahtar Kelimeler: Kıbrıs Türk ağızları, Anadolu ağızları, karĢılaĢtırmalı ağız çalıĢmaları, etnik köken ve ağız, sözlükbirimler, söz varlığı.
Türk Dili ve Edebiyatı Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Fen ve Edebiyat Fakültesi, Türk Dili ve Edebiyatı Bölümü, 2014. Tez Danışmanı: Yard. Doç. Dr. Gülseren Tor.
Keywords: Türk Dili ve Edebiyatı; Türkçe - Ağızlar - Kıbrıs; Kıbrıs Türk ağızları; Anadolu ağızları; karĢılaĢtırmalı ağız çalıĢmaları; etnik köken ve ağız; sözlükbirimler; söz varlığı; Turkish Cypriot dialects; Anatolian dialects; comparative dialect studies; ethnic structure and dialect; lexemes; vocabulary